Measuring Women's Political Empowerment across the Globe Strategies, Challenges and Future Research (Gender and Politics, 2018)
This volume brings together leading gender and politics scholars to assess how women's political empowerment can best be conceptualized and measured on a global scale. It argues that women's political empowerment is a fundamental process of transformation for benchmarking and understanding all political empowerment gains across the globe. Chapters improve our global understanding of women's political empowerment through cross-national comparisons, a synthesis of methodological approaches across varied levels of politics, and attention to the ways gender intersects with myriad factors in shaping women's political empowerment. This book is an indispensable resource for scholars of politics and gender, as well as being relevant to a global scholarly and policy community.